The use of SGLT2 inhibitors in the treatment of cognitive disorders - Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk (Journal of Education, Health and Sport, 2023)
Background:Dementia is a progressive and irreversible disease entity that affects memory, verbal fluency, thinking and the performance of daily activities.The most common type of dementia is alzheimer's disease(AD).Currently, there are no specific therapies with established efficacy against cognitive decline or AD. Objective:The aim of this study is to summarize the current knowledge about the effectiveness of SGLT2 inhibitors(SGLT2i) in the treatment of cognitive disorders. Method and material:The article was created based on the PubMed database and the Polish Journal of Endocrinology.Articles were searched in English using the following keywords: SGLT2ihibitors;dementia;Alzheimer type 3 diabetes mellitus. State of knowledge:Patients with type 2 diabetes (TD2) are 1.5-2 times more likely to develop dementia than the general population.Dementia among diabetic patients is characterized by an earlier age of onset, slightly worse overall cognitive status and a higher prevalence of cognitive impairment in male patients.Diabetes and pre-diabetes shorten the time from the onset of mild cognitive impairment (MCI) to the development of full-blown dementia. Conclusions:The use of SGLT2i is associated with reduced mortality from dementia, in contrast to insulin and sulfonylurea derivatives.SGLT2 inihibitors prevent cognitive impairment more potently than dipeptidylpeptidase-4 inhibitors. Taking empagliflozin for one month, is associated with improved cognitive function and increased scores on the Montreal Cognitive Assessment scale.